Review of the characterization of sodium alginate by intrinsic viscosity measurements: Comparative analysis between conventional and single point methods - Masuelli, Martin Alberto (2014)
In the pharmaceutical and food industry, alginate is used in aqueous solutions and excipients as thickener, gelling agent, coagulant and encapsulant. This biopolymer is very important, with many key industrial applications, especially if the intrinsic viscosity [η] and the viscometric molecular weight (Mv) are known. Alginate is obtained from the cell walls of algae such as Macrocystis pyrifera, Laminaria hyperborea, Laminaria digitata, Laminaria japonica, Sargassum vulgare, etc.; bacteria such as Pseudomonas aeruginosa and Azotobacter vinelandii can also synthesize it. This work studied alginate in aqueous solution from 0.25 to 1% wt., measuring its intrinsic viscosity in order to obtain its Mv. The intrinsic viscosity is calculated by the classical methods of Huggins, Kremer, Schulz-Blashke and Martin. We compared several single point methods to determine which of them would be more appropriate for an alginate-water system. We also obtained Mark-Houwink parameters and the corresponding viscometric molecular weight.